The Commonplace Book of William Byrd II of Westover - A. Lockridge, Kenneth (The University of North Carolina Press, 2014)
William Byrd II (1674-1744) was an important figure in the history of colonial Virginia: a founder of Richmond, an active participant in Virginia politics, and the proprietor of one of the colony's greatest plantations. But Byrd is best known today for his diaries. Considered essential documents of private life in colonial America, they offer readers an unparalleled glimpse into the world of a Virginia gentleman. This book joins Byrd's Diary, Secret Diary, and other writings in securing his reputation as one of the most interesting men in colonial America. Edited and presented here for the first time, Byrd's commonplace book is a collection of moral wit and wisdom gleaned from reading and conversation. The nearly six hundred entries range in tone from hope to despair, trust to dissimulation, and reflect on issues as varied as science, religion, women, Alexander the Great, and the perils of love. A ten-part introduction presents an overview of Byrd's life and addresses such topics as his education and habits of reading and his endeavors to understand himself sexually, temperamentally, and religiously, as well as the history and cultural function of common placing. Extensive annotations discuss the sources, background, and significance of the entries.